1991
DOI: 10.1172/jci114998
|View full text |Cite
|
Sign up to set email alerts
|

An alpha 2-macroglobulin receptor-dependent mechanism for the plasma clearance of transforming growth factor-beta 1 in mice.

Abstract: Radioiodinated transforming growth factor-,61 i1) bound to the plasma proteinase inhibitor, a2-macroglobulin (a2M), as determined by chromatography on Superose-6 and native polyacrylamide gel electrophoresis. When a2M conformational change was induced with methylamine, 1"I-TGF-jfl binding significantly increased. Intravenously injected 125I_ TGF-il cleared from the circulation of mice rapidly at first; however, intravascular radioactivity stabilized near 20% of the initial level. At necropsy, radioactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 33 publications
5
102
0
1
Order By: Relevance
“…Serum stimulation of AtT20 cells also increased DENTT production by 4 hr that peaked at 2.5-fold above DENTT basal levels by 8 hr, and then decreased, whereas only a modest increase in DENTT protein occurred in GH3 or ␣T3-1 cells. Because serum has been shown to contain proteins that can associate and bind TGF-␤1 like ␣2-macroglobulin (LaMarre et al, 1991), our studies suggest that there may be other factors in serum in addition to TGF-␤1 that may also be able to regulate DENTT expression. By using the activin/TGF-␤ -responsive p3TP-Lux Luciferase reporter (Carcamo et al, 1994) that has been shown to be responsive in AtT20, GH3, and ␣T3-1 cells (Yamashita et al, 1995;Bilezikjian et al, 2001), our transient transfection studies showed that DENTT expression significantly increases the level of p3TP-Lux reporter transcription in AtT20 cells but not in GH3 or ␣T3-1 cells.…”
Section: Discussionmentioning
confidence: 86%
“…Serum stimulation of AtT20 cells also increased DENTT production by 4 hr that peaked at 2.5-fold above DENTT basal levels by 8 hr, and then decreased, whereas only a modest increase in DENTT protein occurred in GH3 or ␣T3-1 cells. Because serum has been shown to contain proteins that can associate and bind TGF-␤1 like ␣2-macroglobulin (LaMarre et al, 1991), our studies suggest that there may be other factors in serum in addition to TGF-␤1 that may also be able to regulate DENTT expression. By using the activin/TGF-␤ -responsive p3TP-Lux Luciferase reporter (Carcamo et al, 1994) that has been shown to be responsive in AtT20, GH3, and ␣T3-1 cells (Yamashita et al, 1995;Bilezikjian et al, 2001), our transient transfection studies showed that DENTT expression significantly increases the level of p3TP-Lux reporter transcription in AtT20 cells but not in GH3 or ␣T3-1 cells.…”
Section: Discussionmentioning
confidence: 86%
“…4) and the marked dependence of hepcidin binding to ␣ 2 M/␣ 2 M-MA on pH (Fig. 5, C and D (10,50). Lrp1 is the major receptor responsible for clearance of activated-␣ 2 M from the circulation (18).…”
Section: Hepcidin Binds To ␣ 2 M/␣ 2 M-ma Via a Mechanism Directly Ormentioning
confidence: 93%
“…Administration of activated ␣ 2 M or augmentation of the clearance of the TGF-␤-␣ 2 M complex might be strategies for decreasing TGF-␤ levels. However, it has to be considered that not only TGF-␤, but also many other cytokines such as TNF-␣ and IL-6 bind to ␣ 2 M. 142 What the potential adverse effects are of neutralizing these other cytokines remains to be investigated. Furthermore, it is important to determine whether the ␣ 2 M receptor can be easily saturated, because in this case the ␣ 2 M-TGF-␤ complexes will persist in the circulation.…”
Section: Strategies To Counteract the Negative Immunomodulatory Effecmentioning
confidence: 99%